Computer Specifications Expert System Software As A Tool For Part Replacement Decision Makers - Afero, Yosdarso (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2015)
In troubleshooting Computer Systems the two most common causes of delay are Trial and Error and having Incomplete Information.Â The problems in Computer Systems will be fixed faster if the Possible Cause of the Problem is already known. A solution to this is to use an Expert System. This system can reproduce the ability of an expert to diagnose by giving an accurate recommendation on the possible cause of the problem for effective troubleshooting. To know the Possible Cause of a problem there must be a complete set of information. These data will be the one to be inputted in the Expert System to give an accurate recommendation. A problem is that in reality a complete set of data will not always be obtained. There will be instances when the information gathered will be incomplete.